Community-Based Wound Care Programs for Unhoused Individuals - Taichi Goto; Christina Wang; Catherine Kwiat; Christopher Nguyen; Leorey N. Saligan (Springer, 2023)
Abstract Wound care management for unhoused individuals is challenging due to the lack of healthcare infrastructure to handle the unique needs of this population. Therefore, we aimed to obtain insights for best practices and to establish a care clinic that is low threshold, community-based and meets the needs of unhoused people. We employed two approaches: (1) conduct a targeted narrative review of the literature of existing or proposed community-based program models that can address the wound care needs of unhoused individuals, and (2) assess cost-effectiveness and describe the results of a survey administered to unhoused clients and their health care providers at a community-based wound care program in Honolulu, Hawai'i. The literature search and screening yielded 11 articles relevant to the topic. Per the literature, existing community-based healthcare programs were successful when: (1) wound care services were incorporated into a broader social/health program, (2) cost-effective, and (3) comprehensive services were provided. Survey results in Honolulu found that the wound care program matched the needs of the targeted population and was cost-effective. Difficulty in following clients until wound closure and the sustainability of the program, particularly the lack of insurance reimbursement for street-based services, were perceived challenges. Additionally, the lack of insurance reimbursement for street-based wound care services continues to impact sustainability. Community-based programs can be successful in addressing the wound care needs of unhoused individuals if they address complex fundamental issues. This paper highlights existing gaps in logistics and policies that must be addressed to meet the specific medical needs of these vulnerable individuals.